Development of Health Tourism in Turkey: SWOT Analysis of Antalya Province - Aksu, Akın; BAYAR, Kerem (Journal of Tourism Management Research, 2019)
Health tourism is one of the most important types of alternative tourism that provides sustainable tourism. When examining the coordination among current developments in health tourism in the world, technological innovations, and health tourism providers, it is clear to see that Turkey and Antalya have not yet reached the desired level. This study attempts to evaluate and explain the position of Antalya, which wants to attain a share in health tourism. In this context, a SWOT analysis of Antalya in the development of health tourism was carried out. Antalya is primarily a cheap destination, and this is a very attractive feature for foreign tourists. Health services in Antalya, doctors and other health care personnel, applied treatments, and technological devices are at a very high standard. Tourists who prefer autumn and spring seasons will solve the seasonality problem of Antalya especially during off-peak times. For this purpose, Antalya should additionally be promoted and marketed as a destination for health tourism. In this context, public and private sectors need to cooperate. Within the scope of the responses obtained from the participants, Antalya is required to conduct studies on being easily accessible and reliable for patients. Promotional information in brochures or posters should also be reviewed.